2016
DOI: 10.1063/1.4962426
|View full text |Cite
|
Sign up to set email alerts
|

Resonant and nonresonant vibrational excitation of ammonia molecules in the growth of gallium nitride using laser-assisted metal organic chemical vapour deposition

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…16,[22][23][24][25][26][27][28][29][30] For instance, Iwanaga et al 22 reported the deposition of large-area amorphous silicon films using CO2 laser LMOCVD with a high growth rate of > 60 µm/h in a relatively low laser power and low substrate temperatures. Recently, we have demonstrated the fast growth of GaN films with (0002) preferential orientation using CO2 laser LMOCVD with a growth rate up to 84 µm/h at low temperatures, 26 where the experiments were designed to elucidate the GaN growth mechanism via CO2 laser LMOCVD rather than to optimize the material crystalline quality. The high GaN growth rate is due to the mixed photolysis/pyrolysis reactions of the precursors and the photo-induced effects, as has been evidenced by wavelength dependence of GaN growth rates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16,[22][23][24][25][26][27][28][29][30] For instance, Iwanaga et al 22 reported the deposition of large-area amorphous silicon films using CO2 laser LMOCVD with a high growth rate of > 60 µm/h in a relatively low laser power and low substrate temperatures. Recently, we have demonstrated the fast growth of GaN films with (0002) preferential orientation using CO2 laser LMOCVD with a growth rate up to 84 µm/h at low temperatures, 26 where the experiments were designed to elucidate the GaN growth mechanism via CO2 laser LMOCVD rather than to optimize the material crystalline quality. The high GaN growth rate is due to the mixed photolysis/pyrolysis reactions of the precursors and the photo-induced effects, as has been evidenced by wavelength dependence of GaN growth rates.…”
mentioning
confidence: 99%
“…The high GaN growth rate is due to the mixed photolysis/pyrolysis reactions of the precursors and the photo-induced effects, as has been evidenced by wavelength dependence of GaN growth rates. [25][26][27] However, the low-temperature deposition resulted in films with broad XRD peaks and low crystalline quality. 22,25 The growth of high-quality GaN films suitable for device application were usually realized at high deposition temperatures.…”
mentioning
confidence: 99%
“…[19] Previously, carbon dioxide (CO 2 ) laser was also utilized in GaN MOCVD growth. [20][21][22] At the resonant wavelength of 9.219 μm, strong emissions from NH 2 radicals were observed in the optical emission spectra (OES) from the resonantly excited NH 3 flows, together with other emission peaks from NH, N, N þ , and H, which exhibited an effective dissociation of NH 3 molecules with CO 2 laser irradiation. [22] It demonstrated GaN growth on (0001) sapphire substrate at a very low temperature of 250 C in a custom-designed system.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] At the resonant wavelength of 9.219 μm, strong emissions from NH 2 radicals were observed in the optical emission spectra (OES) from the resonantly excited NH 3 flows, together with other emission peaks from NH, N, N þ , and H, which exhibited an effective dissociation of NH 3 molecules with CO 2 laser irradiation. [22] It demonstrated GaN growth on (0001) sapphire substrate at a very low temperature of 250 C in a custom-designed system. Fast GaN GRs of 12 [21] and 84 μm h À1 [22] were demonstrated using CO 2 laser at the growth temperature of 600 and 750 C, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation